Ideologi Negara Sebagai Perekat dan Kesatuan Bangsa - Tinasyah, Amanda Anggraini (Maliki Interdisciplinary Journal, 2025)
This paper examines the function of state ideology, especially Pancasila, as a binder and unifier of the Indonesian nation amid social, cultural and political diversity. Pancasila, as the foundation of the state and the guiding values of community life, serves to maintain the integrity and unity of the nation by instilling a spirit of tolerance, justice, and togetherness among diverse communities. The principles contained in each of the Pancasila precepts serve as a reference in resolving disputes and differences, thus preventing divisions and strengthening national integration. In facing the challenges of globalization, information flow, and changing times, understanding and applying the values of Pancasila remain important to build a strong and harmonious national character. In other words, the state ideology not only serves as an identity, but also as the main basis in maintaining the unity and integrity of the Indonesian nation.